(untitled) (Agroindustrial Science, 2024)
The objective of this study was to evaluate the differences between three species of the genus Orestias (O. luteus, O. olivaceus and O. agassii) in biometry, proximal macronutrient composition and fatty acid profile. A total of 90 fish were used and total length (TL), standard length (LE) and total weight (W) were measured (n = 30 per species), and 10 fish for each group were measured at random to determine fatty acids. The results showed significant differences (p < 0.05) between species; the highest value was obtained by Orestias agassii (TL of 13.00 ± 0.14 cm, LE of 11.86 ± 0.91 cm and W of 27.54 ± 2.78 g). For fatty acids, slightly high values ​​were evident in PUFA (38.56 ± 0.81%), LC PUFA n-3 (25.70 ± 0.28%) and LC PUFA n-6 (13.92 ± 0.81 %) in O. luteus. A higher content of vaccenic acid (18:1ω11) was also found in O. agassii (6.04 ± 0.01 g 100-1 fatty acid), corresponding to a higher intake of algae. It is recommended to develop work on the enrichment of EPA + DHA sources in feed for these species to demonstrate their aquaculture potential, in the search for healthy nutrition for aquatic species.